2001년 11월 오염시기와 2002년 봄 황사시기 제주도 고산에서의 미량원소 농도 변화 - 한진석; 김영성; 문광주; 안준영; 김정은; 류성윤; 김영준; 공부주; 이석조 (한국대기환경학회, 2004)
The chemical composition of PM2.5 was measured at Gosan. Jeju for two weeks each in November 2001 and spring 2002. In the latter part of the measurement period of November 2001, designated as the polluted period in this work, secondarily formed ion components as well as primarily emitted elemental carbon were high, PM2.5 mass concentration was also high in this polluted period compared with the yellow sand period, in which daily average of PM10 peaked up to 520㎍/㎥. Increase of major components of anthropogenic origin in the polluted period was not correlated with the variation in sea salt components while increase of crustal components in the yellow sand period was highly correlated with the variation in sea salt components. Trace elements were generally higher in the yellow sand period: however, toxic heavy metals such as zinc, cadmium and lead were the highest in the polluted period.